Microbiology : With Diseases by Taxonomy - Bauman, Robert W (Pearson/Benjamin Cummings, 2007)
With research that highlight the intrinsic appeal of microbiology, this book contains an art program, includes a "Microbe-at-a-Glance" feature, offers options for the Microbiology Place website/CD-Rom, and provides instructors with a Media Manager presentation package with 30 multi-step animations.